Microfinance in Eastern India: The Role Played by Regional Rural Banks - Das, Sulagna; Patnaik, B. C. M. (Indian Journal of Finance, 2015)
The present paper studied the microfinance status of the regional rural banks of Eastern India, which included the states of Bihar, Jharkhand, Odisha, and West Bengal for 3 years. The study was based on secondary data. To study made a comparative analysis with respect to the number of self-help groups, savings amount of the SHGs, total loan disbursed by SHGs, outstanding loan and NPAs of the SHGs for SHG scheme, SHG under SGSY scheme, and WSHG scheme. Lastly, the study also made an attempt to analyze and interpret the reasons for the differences.